2018
DOI: 10.1016/j.tips.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Targeted Therapeutics for Metabolic Disease

Abstract: Macrophages are cells of the innate immune system that are resident in all tissues, including metabolic organs such as the liver and adipose tissue (AT). Because of their phenotypic flexibility, they play beneficial roles in tissue homeostasis, but they also contribute to the progression of metabolic disease. Thus, they are ideal therapeutic targets for diseases such as insulin resistance (IR), nonalcoholic fatty liver disease (NAFLD), and atherosclerosis. Recently, discoveries in the area of drug delivery hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 99 publications
(93 reference statements)
0
76
0
Order By: Relevance
“…Therefore, in contrast to hepatocyte Sort1 deficiency, myeloid Sort1 deficiency did not seem to provide beneficial effects in maintaining lipid homeostasis and reducing pro-inflammatory response in WD-fed mice. Macrophages play important roles in the pathogenesis of fatty liver disease (40). How macrophage Sort1 deficiency may alter macrophage function to promote hepatocyte lipid accumulation upon WD feeding requires further investigation and is out of the scope of the current study.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Therefore, in contrast to hepatocyte Sort1 deficiency, myeloid Sort1 deficiency did not seem to provide beneficial effects in maintaining lipid homeostasis and reducing pro-inflammatory response in WD-fed mice. Macrophages play important roles in the pathogenesis of fatty liver disease (40). How macrophage Sort1 deficiency may alter macrophage function to promote hepatocyte lipid accumulation upon WD feeding requires further investigation and is out of the scope of the current study.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The tissue macrophages at maternal‐foetal interface are named placental Hofbauer cells. The M1 and M2 profile is different during pregnancy progress, and changes in this balance have been associated with obstetric and metabolic disorders …”
Section: Introductionmentioning
confidence: 99%
“…The M1 and M2 profile is different during pregnancy progress, and changes in this balance have been associated with obstetric and metabolic disorders. 16,20 Dendritic cell (DC) seems to play a critical role in pregnancy development; its interaction with Tregs has been associated with the process of foetal-maternal tolerance. 21,22 Likewise, impaired function and/or number of DC have been demonstrated in obstetric pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are cells involved in the innate immune system that respond to acute infections and maintain tissue homeostasis by secreting specific chemokines and cytokines . A variety of studies have shown that tissue macrophages can regulate insulin sensitivity in various target tissues such as adipose tissue (e.g., ATM), liver (e.g., Kupffer cells [KCs]), and brain (e.g., microglia).…”
Section: Macrophage Phenotypes and Characteristicsmentioning
confidence: 99%